A self-perceived analysis of students intelligence and academic achievement - Mohamad, Siti Nurul Mahfuzah; Salam, Sazilah; Bakar, Norasiken; Jusoff, Kamaruzaman; Ahmad, Rabiah; Mohd Salleh, Mohd Azran; Yusoff, Mariana; Khoo, Linda Mei Sui (American-Eurasian Network for Scientific Information, 2013)
Multiple Intelligences (MI) are eight different ways to demonstrate intellectual ability. It is how human learn best and apply to daily activities. The theory states that every human has at least two or more intelligences, for example, verbal-linguistic, logic-mathematic, intrapersonal, interpersonal, visual-spatial, musical, natural and existential intelligences. The objective of this paper is to identify and analyse the relationship between students’ intelligence and academic achievement among polytechnic students. The theories of MI are used in this study where the instrument used was Ujian Multiple Intelligence (UMI) which showed a positive correlation between their intelligence and academic achievement. The correlation for interpersonal, verbal-linguistic, bodily-kinesthetic, visual-spatial and musical is at a moderate rate while naturalistic, intrapersonal and logic-mathematic is weak. It is highly recommended that educators, although with minimal knowledge of Information Technology (IT), use the online MI teaching tools in the teaching and learning aspect.